Fire prevention methods by the reason of casual handling with fire during smoking - Sizikov, Алексей Сергеевич (Chrezvychaynye situatsii: obrazovanie i nauka, 2007)
The basic Fire prevention methods by the reason of casual handling with fire during smoking were examined. Approaches which allow to minimize numbers of fires by this reason and also minimize injuring and loss of life were offered.